1994
DOI: 10.1093/cvr/28.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy causes delayed conduction in human and guinea pig myocardium: accentuation during ischaemic perfusion

Abstract: Delayed conduction is an important feature of severe cardiac hypertrophy in guinea pigs and man. Hypertrophy is associated with accentuated conduction delay and altered repolarisation during ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 0 publications
3
43
0
Order By: Relevance
“…QRS duration was increased 10 and CV decreased 11 in a guinea pig model of HF at day 150 after aortic banding; however, in the same model, CV was increased after 50 days of aortic banding. 11 This underscores the dynamic nature of HF.…”
Section: Clinical Perspective P 813mentioning
confidence: 79%
See 2 more Smart Citations
“…QRS duration was increased 10 and CV decreased 11 in a guinea pig model of HF at day 150 after aortic banding; however, in the same model, CV was increased after 50 days of aortic banding. 11 This underscores the dynamic nature of HF.…”
Section: Clinical Perspective P 813mentioning
confidence: 79%
“…In guinea pig after 150 days of aortic constriction, heart size, QRS duration, 10 and intracellular resistivity 40 were increased and CV 11 was decreased. In a milder stage of HF (50 days of aortic constriction), heart size and CV were increased, 11 whereas intracellular resistivity 40 and QRS width 10 were unchanged.…”
Section: Conduction Velocitymentioning
confidence: 95%
See 1 more Smart Citation
“…The operation was performed under anaesthesia (0-22 ml kg-' sodium pentobarbitone, followed by inhalation of a 49:49:2 N20 :02: halothane mixture) and the animal subsequently allowed to recover with post-operative analgesia (50 jug kg-' subcutaneous buprenorphine) given after wound closure. A sham (control) group, with no clip, underwent the same operative procedure (for further details see Winterton et al 1994). …”
Section: Methodsmentioning
confidence: 99%
“…Left ventricular hypertrophy induced by thoracic aortic constriction is accompanied by reduced conduction velocity, which can be explained by an increased intracellular resistivity, specifically a raised cell-to-cell resistance, and contributes to the resultant arrhythmias (Winterton, Turner, O'Gorman, Flores & Sheridan, 1994;Cooklin, Wallis, Sheridan & Fry, 1995). To evaluate the cellular basis of this phenomenon, intracellular pH (pHi) was measured in isolated myocytes from such hearts, since it has been shown that a decrease of pHi increases gap junction resistance in cell pairs (White, Spray, Campos de Carvalho, Wittenberg & Bennett, 1981).…”
Section: Introductionmentioning
confidence: 99%